Educação Ambiental no curso de Pedagogia: A formação socioambiental do professor - Resende, Guilherme Dalla Mutta (2023)
Taking as a reference the need for critical environmental education in the training of pedagogues, the objective of this work was to develop a virtual educational product, a guide entitled “Socio environmental Education Guide for Early Childhood Education and Elementary Education - Early Years” with the aim of assisting these professionals in Early Childhood Education and the initial grades of elementary school. We use the Google Sites tool. The guide has 65 works distributed in the following categories: Experience report; Research Report; Teaching Activities and Products; Digital book; Software. Thirty-eight pedagogues, in-service teachers, evaluated the aforementioned product and their responses demonstrate interest in EA. The data also suggest that EA macrotrends should be addressed in initial teacher training, especially critical EA, as this aspect has not reached them, thus confirming our hypothesis. The digital tool was well evaluated by these participants, who also offered relevant suggestions for improving the guide.